DIGITIZATION OF LEARNING IN THE RURAL SCHOOL (Computer Based Learning Implementation at SMP Cendikia Sukahegar Sukaluyu Cianjur West Java Indonesia) - Nugraha, Dera; Ruhimat, Devi C (Jurnal Pendidikan Dasar Setiabudhi, 2020)
Digitization of learning is one of the todays’ challenges being faced by Indonesian schools, including rural schools. This reasearch aims to implement and measure the effectiveness of computer based learning at SMP Cendikia Sukahegar, recognize its challenges, and find the appropriate computer based learning model for them. The method used is experimental research based on descriptive qualitative approach, using instruments of observation, interview, and document analysis. The results of this study show that computer based learning at SMP Cendikia Sukahegar improves their student learning outcomes. The appropriate computer based learning model is instructional game. Meanwhile, the problems faced in the implementation of computer based learning are related to human resources, facilities, and supporting policies from the principals. Keywords: Computer based learning, digitization, rural school Abstrak Digitalisasi pembelajaran merupakan salah satu tantangan yang saat ini dihadapi oleh sekolah-sekolah di Indonesia, termasuk sekolah pedesaan. Penelitian ini bertujuan untuk mengimplementasikan dan mengukur keefektifan pembelajaran berbasis komputer di SMP Cendikia Sukahegar, mengenali tantangannya, dan menemukan model pembelajaran berbasis komputer yang sesuai untuk mereka. Metode yang digunakan adalah penelitian eksperimental berdasarkan pendekatan kualitatif deskriptif, dengan menggunakan instrumen observasi, wawancara, dan analisis dokumen. Hasil penelitian ini menunjukkan bahwa pembelajaran berbasis komputer di SMP Cendikia Sukahegar dapat meningkatkan hasil belajar siswa. Model pembelajaran berbasis komputer yang sesuai adalah permainan instruksional. Sedangkan permasalahan yang dihadapi dalam pelaksanaan pembelajaran berbasis komputer terkait dengan sumber daya manusia, fasilitas, dan kebijakan pendukung dari kepala sekolah. Kata kunci: Pembelajaran berbasis komputer, digitalisasi, sekolah pedesaan